2021
DOI: 10.47487/apcyccv.v2i1.126
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Bayés, accidente cerebrovascular y demencia

Abstract: El síndrome de Bayés es una entidad clínica que se define como la asociación entre la presencia de bloqueo interauricular avanzado (BIA-A), y el desarrollo de taquiarritmias supraventriculares (TSV), siendo la fibrilación auricular (FA), la más frecuente. Esta asociación salió a la luz con los estudios del Prof. Antoni Bayés de Luna en los años ‘80. Estudios realizados posteriormente por otros grupos encontraron una fuerte asociación entre este síndrome y la ocurrencia de fenómenos tromboembólicos, siendo el a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(178 reference statements)
0
3
0
Order By: Relevance
“…The BAYES registry, which included 137 patients with advanced IAB, after a mean follow-up of 694 days, reported a HR of 3.8 for stroke (95% CI: 1.4-10.7) and of 2.6 for AF with stroke (95% CI: 1.5-4.4) 5 . An increase of up to 5 times in the risk of cognitive impairment has been described, possibly in relation to stroke, silent infarctions, and cerebral hypoperfusion 10 . High recurrence rates have also been demonstrated after pulmonary veins isolation for AF and recurrence of up to 90% after cardioversion 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BAYES registry, which included 137 patients with advanced IAB, after a mean follow-up of 694 days, reported a HR of 3.8 for stroke (95% CI: 1.4-10.7) and of 2.6 for AF with stroke (95% CI: 1.5-4.4) 5 . An increase of up to 5 times in the risk of cognitive impairment has been described, possibly in relation to stroke, silent infarctions, and cerebral hypoperfusion 10 . High recurrence rates have also been demonstrated after pulmonary veins isolation for AF and recurrence of up to 90% after cardioversion 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation is not recommended in patients with advanced IAB with no evidence of AF; in these cases, extensive monitoring should be carried out to actively search for arrhythmia. Two clinical trials are underway, ARCADIA, and AMIABLE, which seek to define the benefit of anticoagulation in patients without AF but with risk factors for or with atrial cardiomyopathy 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated a strong relationship between IAB or Bayes' syndrome and thromboembolic phenomena, with cardiovascular and neurological consequences. Regarding neurological involvement, patients with IAB or Bayes' syndrome have an increased incidence of ischemic events, cognitive impairment, and dementia [4][5][6] . These observations triggered the hypothesis that the early use of anticoagulation and antiarrhythmic therapy could have benefits in patients with IAB before the documentation of AF 7 .…”
Section: Introductionmentioning
confidence: 99%